The Influence of Independence and Audit Experience on Audit Judgment with Task Complexity as a Moderating Variable at the Financial and Development Supervisory Board (BPKP) Representative of the DKI Jakarta Region, Indonesia - Jajang Gunawan; Napisah Napisah (Lafadz Jaya Publisher, 2024)
This research aims to determine the influence of independence and audit experience on audit judgment with task complexity as a moderating variable at the Financial and Development Supervisory Board (BPKP) Representative of DKI Jakarta Region, Indonesia. This research uses a quantitative type of research using a population of 60 auditors with a sample of 53 auditors at the Financial and Development Supervisory Board (BPKP) Representative of DKI Jakarta Region, Indonesia (Audit Division of P3A Corps, APD Corps, Investigation Corps, AN Corps and IPP Corps). Data collection techniques use questionnaires, observation, and literature study. Data analysis uses Partial Least Square (PLS) with the SMARPLS 4.0 application. The results of the research show that independence and audit experience have a significant effect on audit judgment. The results also show that task complexity is unable to moderate the effect of independence and audit experience on audit judgment.